Use of plant residues for improving pod chemical composition, biochemical quality and pod yield of okra (Abelmoschus esculentum L.) - E. I., Moyin Jesu (Universiti Putra Malaysia Press, 2006)
The effect of wood ash, saw dust, ground cocoa husk, spent grain and rice bran used ordinarily on the okra pod, chemical composition, biochemical quality and pod yield ofokra (Abelmoschus esculentum Moench) variety NHAe47 was studied. Five organicfertilizer treatments were compared to a chemical fertilizer (1,600 kg/ha NPK 15-15-15) and unfertilized controls in four field experiments. The treatments were replicated four times and arranged in a randomized complete block design for each experiment. The chemical composition ofthe organic materials, pod nutrients, biochemical quality, and pod yield of okra were determined for the different treatments. The results showed that the application of6 t/ha ofplant residues significantly (P< O. 05) increased the pod yield, N, P, K, Ca, Mg, Na, ash, crude protein and pod yield ofokra compared to the control treatment. Wood ash, cocoa husk and spent grain were the most effective in improving pod yield, pod nutrient status and biochemical quality while the rice bran and saw dust were least effective. The plant residues produced better pod Ca, Mg and Na contents than the NPK 15-15-15 fertilizer treatment.